The Correlation of Maternal Knowledge and Attitudes Towards Serology Screening Management for Pregnant Women at the Wisata Hospital of the Indonesia Timur University - Jurnal Syarif; Hasanuddin, Asni (International Journal of Public Health Excellence (IJPHE), 2022)
Every pregnant woman will face the risk of complications that can threaten her life. The purpose of this study is to determine the relationship between knowledge and attitudes toward the implementation of serological screening (HIV, Syphilis, Hepatitis B, and Rubella) in pregnant women at the Tourism Hospital, University of East Indonesia. This type of research is quantitative analytical research with a cross-sectional approach. The population in this study consisted of all pregnant women registered at the University of East Indonesia Tourism Hospital from January to June 2022 with a total of 42 respondents. Using purposive sampling techniques, 42 samples were taken. Data were collected with questionnaires and observation sheets. Data were analyzed by univariate and bivariate analysis with a chi-square test. The results showed that 23 respondents (54.8%) had poor knowledge, 24 respondents (57.1%) had negative attitudes, and 24 respondents (57.1%) had abnormal serological screening results. Based on the results of statistical analysis, it was found that there was a relationship between knowledge (p-value 0.001 <0.05) and attitudes (p-value 0.003 <0.05) toward the implementation of serological screening in pregnant women. Therefore, women can know and always do serological screening regularly and according to gestational age.